DEVELOPMENT OF ALGORITHM FOR CHOOSING A RATIONAL FACADE SYSTEM OF MULTI-STOREY BUILDINGS - Radkevych, A. V.; Tkach, T. V.; Netesa, K. M. (Science and Transport Progress, 2021)
Purpose. The authors aimed to form an algorithm for choosing a rational facade system for a specific construction site, taking into account climatic, organizational-technological and operational properties, applicable to use by any participant in the construction process. Methodology. The criteria for choosing a rational facade system were determined. The state of choosing and applicability of modern facade systems for new construction and overhaul in Ukraine was analyzed. Based on certain factors influencing the choice of the most rational facade system of a multi-storey residential or public building the authors formed a convenient and objective algorithm for choosing a facade system, taking into account the main features of the construction object, as well as operating parameters. The algorithm was adapted to practical application. Findings. The influence of the parameters of choosing facade system on the process of arrangement, operation and repair of the modern facade system is established. The obtained algorithm for choosing a rational facade system by an estimation of values of influence factors in activity of the leading design organizations of Dnipro was successfully tested. By passing the appropriate algorithms at the joint meetings of the designer, customer and contractor, the most rational facade systems were found for specific construction projects with significant objectivity of choice. The adaptability of the algorithm by discarding minor factors leads to increased visibility of the process of choosing a facade system. Originality. The regularity of the influence of a number of organizational-technological and operational factors on the process of choosing a rational facade system is established. The efficiency of determining the appropriate system for specific construction conditions has been increased, taking into account the peculiarities of operation and purpose of the building. Practical value. The participant of construction by passing a simple algorithm has the opportunity to clearly assess the influence of organizational, technological and operational factors on the choice of a rational facade system. By evaluating the parameters of the corresponding factors, the most rational facade system for a particular object was determined. As a result, the cost of operation of the facade system is significantly reduced while optimizing the duration of repair periods and improving the working conditions of the components of the facade system.